Insight into the structural and functional features of myoglobin from Hystrix cristata L. and Rangifer tarandus L.1. Issue 33 (12th April 2015) - Di Giuseppe, Antonella M. A.; Caso, Jolanda V.; Severino, Valeria; Ragucci, Sara; Chambery, Angela; Russo, Rosita; Fattorusso, Roberto; Ferreras, José M.; Russo, Luigi; Di Maro, Antimo
<x xml:space="preserve">Abstract</x> Myoglobins (Mbs) from Hystrix cristata L. and Rangifer tarandus L. have been isolated and characterised.